The Integration of Al-Ghazali’s Ta’dib Framework in Shaping the Contemporary Pesantren Curriculum: Insights from Indonesia - Pahlawati, Eny Fatimatuszuhro; Amin, Al; Munip, Al; Muttaqin, Muttaqin; Wardono, Boby Hendro; Rozak, Abdul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Pesantren in Indonesia are increasingly challenged by modernization, state-driven standardization, and globalization, which have fragmented religious and secular knowledge, marginalizedmoral and spiritualformation, and reduced educationto merecredentialism—developments that contradict Imam al-Ghazali’s classical vision of ethical and spiritual refinement. To address these challenges, this study proposes a practical model for integrating al-Ghazali’s ta’dib framework—emphasizing adab (discipline), tazkiyah (spiritual purification), mujāhadah (inner struggle), niyyah (sincerity), and ma‘rifah (divine knowledge)—into contemporary pesantren curricula and evaluates its effectiveness through measurable indicators. Adopting a qualitative dual-method design, the research combines hermeneutical analysis of al-Ghazali’s seminal works (Iḥyā’ ‘Ulūm al-Dīn, Ayyuhā al-Walad, al-Tarbiyah wa al-Ta‘līm, al-Risālah al-Ladunniyyah) with field-based case studies in three purposively selected pesantren. Data were collected through semi-structured interviews (n=12), participant observations, and document analysis, and subjected to thematic coding. The study addresses three key gaps in the literature: the absence of empirical implementation models, the lack of rigorous evaluation frameworks, and limited stakeholder-driven research. From field validation, a ta’dib integration model with seven quantifiable indicators was developed—moral reasoning, spiritual disposition, academic performance, pedagogical coherence, stakeholder satisfaction, institutional alignment, and ritual engagement. Findings revealed significant improvements in student character scores (18%) and academic achievement (12%) after one year. Key enabling factors included strong kyai leadership and community involvement, while barriers stemmed from accreditation demands and insufficient teacher training. The results suggest that systematic ta’dib integration can alignspiritual and moralformation with academic excellence, offering evidence-based guidance for pesantren leaders and policymakers in advancing holistic, value-based educationalreform.